Schitt$ Creek. Season 4 [videorecording (DVD)] - Levy, Eugene, 1946-; O'Hara, Catherine; Levy, Daniel, 1983-; Levy, Daniel, 1983-; Murphy, Annie, 1986- (Lions Gate Entertainment Inc., 2020)
Fully entrenched in their new lives, the once-rich Roses find themselves surrounded by family problems -- namely love and death. David and Patrick navigate a deepening romance as Patrick makes a very public overture at an open mic, then is surprised when Alexis unknowingly invites Patrick's ex-fiance to the boys' monthiversary barbeque. Alexis' PR consulting firm takes off with a marketing strategy for the hotel and a singles' week event that puts her back in front of both Mutt and Ted. Jocelyn and Roland are expecting a new baby while Moira thinks she accidentally killed a guest, then faces social media rumors of her own passing.